On the logics and the essence of interrelation of some school subjects - Vaitkevičius, J. (Psichologija, 1963)
Key knowledge necessary for cognition of the reality is received by a person at school. International and especially soviet school experience of historical development has shown that the best way of teaching students is teaching by subjects. The content of an individual subject reflects the content of the relevant science which investigates a certain area of reality. Therefore, by learning different subjects, students deeply perceive the corresponding sides of reality. However, a subject and the system of knowledge it encompasses is not a copy of a certain science. Taking into consideration general goals of education and peculiarities of students’ age, the educational system is pedagogically rearranged, i.e. the logic of the subject does not coincide with the logic of the science. Depending on the students’ thinking peculiarities, the concepts of different sciences are formed in students’ minds not straight away, but gradually, by studying various themes of the school subject. Hence the significance of the inner logic of the subject results, i.e. aspiration to establish the system of inner relations of each subject taught. However, a separate science investigates only a small part of the world, so studying a school subject introduces students to a separate part of the reality. A full view of life and reality is perceived by students by learning different school subjects and connecting all kinds of knowledge into one whole. The content analysis of various school subjects reveals that apart from concepts formed in the course of study of a single subject, there are many concepts of an interdisciplinary character which form in the study courses of various subjects. Therefore, the logic of the learning process does not end up with one subject logic. Actual successful assimilation of concepts and developed learning needs clearly established interdisciplinary relations. We have investigated the formation of the concepts of water and air in the curricula of eight-year school geography, botany, physics, and chemistry lessons. The results showed that in every study course of these subjects our investigated concepts are analyzed in a number of themes in this way helping to acquire deeper and deeper meanings. But each subject teaches these concepts by considering the goals of the science reflected by the relevant school subject. New subjects are not taught in a vacuum. They basically stem out from the previous ones and at the same time expand and supplement the already possessed knowledge by revealing new and new sides of seemingly the same concepts. Full disclosure of the content of the concepts we are investigating is only possible by connecting the knowledge of different subjects. Close interdisciplinary relations existing among botany, geography, physics, and chemistry while investigating the content of the concepts water and air in eight-year school is demonstrated by the data about difficulties faced by the teachers of these subjects. The majority of the questioned teachers teaching physics in the 6th grade and chemistry in the 7th grade have indicated the same difficulties as the 5th grade botany and geography teachers. Only in rare cases did senior grades’ teachers reported on difficulties of a new character. Consequently, the difficulties faced in junior grades reappear in senior grades when learning new related subjects. Therefore, for improvement of the learning process and overcoming difficulties typical for learning of several subjects, it is necessary to establish tight interdisciplinary relations, i.e. respect the logics of all the learning process. While establishing interdisciplinary relations in learning, the main role can be played by curricula. For this purpose, the curricula must not only establish the quantity of knowledge, competences and skills necessary for students learning a certain subject, but also to disclose the structure of such knowledge, competences and skills, main ideas of the course and explain the ideas shared by relative subjects. Course books on individual subjects must provide questions and tasks, directing a teacher and students to interdisciplinary relations. In the learning process, it is necessary to draw teachers’ attention to application of students’ experience in lessons, the organization of their practical activity, laboratory and practical works, especially the complex ones.